2023
DOI: 10.1111/cen.14861
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal incidentaloma: Do patients with apparently nonfunctioning mass or autonomous cortisol secretion have similar or different clinical and metabolic features?

Abstract: Objective Although there is growing evidence associating nonfunctioning adrenal incidentalomas (NFAI) with cardiovascular risk factors, there are limited data whether NFAI and autonomous cortisol secretion (ACS) groups have similar or different clinical and metabolic features. The aim of this study is to compare cardiometabolic clinic parameters among patients with ACS and NFAI, as well as controls. Design Cross‐sectional study. Patients Eighty nine NFAI, 58 ACS and 64 controls were evaluated. Measurements Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the study by Rabelo et al patients with AI presented higher frequency of hypertension (74.1 vs. 57.8%; p = 0.02), resistant hypertension (45.4 vs. 9.4%; p < 0.001) compared to the controls, respectively. NFAI and ACS patients presented similar frequency of arterial hypertension (70.8 vs. 79.3%) and resistant hypertension (41.3 vs. 51.1%) [41].…”
Section: Discussionmentioning
confidence: 86%
“…In the study by Rabelo et al patients with AI presented higher frequency of hypertension (74.1 vs. 57.8%; p = 0.02), resistant hypertension (45.4 vs. 9.4%; p < 0.001) compared to the controls, respectively. NFAI and ACS patients presented similar frequency of arterial hypertension (70.8 vs. 79.3%) and resistant hypertension (41.3 vs. 51.1%) [41].…”
Section: Discussionmentioning
confidence: 86%
“…An additional important limitation is the absence of a comparison group from the general population, which indeed makes it challenging to conclusively assert that the worsening of arterial hypertension and hyperglycemia was specifically due to the AI presence instead of being merely a reflection of the natural aging process. However, studies have shown that patients with AI exhibited a higher prevalence of these comorbidities compared to age-matched controls without AI (60)(61)(62)(63), supporting the notion that AI may contribute to these outcomes more than age alone. Future research should aim to incorporate a comparison to more definitively ascertain the specific impact of AI on the development of cardiometabolic complications.…”
Section: Discussionmentioning
confidence: 94%